Digital Electronics/ 2-valued Boolean algebra and it’s theorem in Digital Logic with easy explanation.
Contents
- 1 2-Valued Boolean Algebra & Its Theorems in Digital Logic
- 2 What is 2-Valued Boolean Algebra?
- 3 Basic Boolean Operations
- 4 1⃣ AND Operation (⋅)
- 5 2⃣ OR Operation (+)
- 6 3⃣ NOT Operation (¬ or ‘)
- 7 Boolean Algebra Theorems
- 8 1⃣ Identity Law
- 9 2⃣ Null Law
- 10 3⃣ Idempotent Law
- 11 4⃣ Involution Law
- 12 5⃣ Complement Law
- 13 6⃣ Distributive Law
- 14 7⃣ Absorption Law
- 15 8⃣ De Morgan’s Theorems
- 16 Example: Simplify the Expression
- 17 Summary
- 18 Digital Electronics/ 2-valued Boolean algebra and it’s theorem in Digital Logic with easy explanation.
- 19 01. Boolean Algebra and Logic Gates.pmd
- 20 UNIT-II Boolean algebra and Logic Gates
- 21 Boolean Algebra and Logic Gate
2-Valued Boolean Algebra & Its Theorems in Digital Logic
What is 2-Valued Boolean Algebra?
Boolean Algebra is a mathematical system used in digital electronics where variables take only two values:
All digital circuits (AND, OR, NOT gates) use Boolean algebra to simplify logic expressions.
Basic Boolean Operations
1⃣ AND Operation (⋅)
- Symbol: Aâ‹…BA \cdot B or ABAB
- Truth Table:
A B A â‹… B 0 0 0 0 1 0 1 0 0 1 1 1 - Example: 1â‹…1=1,1 \cdot 1 = 1, 0â‹…1=00 \cdot 1 = 0
2⃣ OR Operation (+)
- Symbol: A+BA + B
- Truth Table:
A B A + B 0 0 0 0 1 1 1 0 1 1 1 1 - Example: 1+0=1,1 + 0 = 1, 0+0=00 + 0 = 0
3⃣ NOT Operation (¬ or ‘)
- Symbol: A′A’ or ¬A\neg A
- Truth Table:
A A’ 0 1 1 0 - Example: 1′=0,1′ = 0, 0′=10′ = 1
Boolean Algebra Theorems
These theorems help in simplifying logic circuits.
1⃣ Identity Law
- A+0=AA + 0 = A
- Aâ‹…1=AA \cdot 1 = A
2⃣ Null Law
- A+1=1A + 1 = 1
- Aâ‹…0=0A \cdot 0 = 0
3⃣ Idempotent Law
- A+A=AA + A = A
- Aâ‹…A=AA \cdot A = A
4⃣ Involution Law
- (A′)′=A(A’)’ = A
5⃣ Complement Law
- A+A′=1A + A’ = 1
- A⋅A′=0A \cdot A’ = 0
6⃣ Distributive Law
- Aâ‹…(B+C)=(Aâ‹…B)+(Aâ‹…C)A \cdot (B + C) = (A \cdot B) + (A \cdot C)
- A+(Bâ‹…C)=(A+B)â‹…(A+C)A + (B \cdot C) = (A + B) \cdot (A + C)
7⃣ Absorption Law
- A+(Aâ‹…B)=AA + (A \cdot B) = A
- Aâ‹…(A+B)=AA \cdot (A + B) = A
8⃣ De Morgan’s Theorems
- (A⋅B)′=A′+B′(A \cdot B)’ = A’ + B’
- (A+B)′=A′⋅B′(A + B)’ = A’ \cdot B’
Example: Simplify the Expression
Expression: A+(Aâ‹…B)A + (A \cdot B)
Using Absorption Law:
A+(Aâ‹…B)=AA + (A \cdot B) = A
So, instead of using a circuit with AND and OR gates, we can directly use A, saving hardware.
Summary
Would you like circuit diagrams or more solved examples?